Investigation of Legal Terms in Modern English and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the investigation of terms and its specific features in Modern English. It also studies peculiarities of legal terms and usage of them in different texts